Edukacja medialna w zmieniającym się społeczeństwie informacyjnym = Media education in a changing information society - Nowicka, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article touches on an extremely important issue, which is the need for media education in pre-school and early school education. The growing popularity of media and multimedia is visible in the activities undertaken by children and young people. The aim of theoretical considerations is to draw attention to the need to implement the principles of media education in the family and school environments. These two environments, which are closest and most important for the child, can best and most effectively prepare young media users for harmonious development in a world dominated by media
Keywords: edukacja medialna; dziecko; szkoła; rodzina; nauczyciele; media education; child; family; school; teacher